The Global Financial Crisis and the Banking System of Russia: Problems and Prospects - Karaev, Alan K.; Guseva, Anna I.; Drozdova, Anna A.; Tkacheva, Olga A.; Rogova, Tatyana M. (International Journal of Economics and Financial Issues, 2016)
Russia’s banking system is one of the most important for the country’s economic development systems and developing dynamically. The banking system in each country reflects its economic and financial situation, the first responding to the UPS and downs in the national and global economy. The stable development of the banking sector ensures the stability of the entire state. Meanwhile, the crises affecting the banking system can change the growth prospects of national economies, resulting in ensuring the financial stability of the state is the basis of its development. Over the past two decades, the banking system of different levels of development of States faced financial turmoil, destabilizing national financial markets. Being in the center of economic life, serving the interests of manufacturers, banks mediate communication between industry and trade, agriculture and population. Banks play a huge role in further deepening and improvement of market relations in the country. Keywords: economic crisis, banking system, Russia, global financial crisis, economic development JEL Classifications: L83, Z30, Z32, F63